Real-life experience with ceftolozane/tazobactam in Canada: results from the CLEAR (Canadian LEadership on Antimicrobial Real-life usage) registry. (June 2021) - Zhanel, George G.; Dhami, Rita; Baxter, Melanie; Kosar, Justin; Cervera, Carlos; Irfan, Neal; Zvonar, Rosemary; Borgia, Sergio; Tessier, Jean-Francois; Dow, Gordon; Ariano, Robert; Dube, Maxime; et al.
Highlights: Use of ceftolozane/tazobactam (C/T) in Canadian patients using data captured by the CLEAR registry. C/T is used as directed therapy to treat a variety of severe infections caused multidrug-resistant Pseudomonas aeruginosa . C/T is commonly used combined with other antimicrobials, with relatively high cure rates and an excellent safety profile. ABSTRACT: Objectives: Ceftolozane/tazobactam is a cephalosporin/β-lactamase inhibitor combination with activity against Gram-negative bacilli. Here we report the use of ceftolozane/tazobactam in Canada using a national registry. Methods: The CLEAR registry uses a REDCap TM online survey to capture details associated with clinical use of ceftolozane/tazobactam. Results: Data from 51 patients treated in 2020 with ceftolozane/tazobactam are available. Infections treated included hospital-acquired bacterial pneumonia (37.3% of patients), ventilator-associated bacterial pneumonia (15.7%), bone and joint infection (11.8%), complicated intra-abdominal infection (7.8%) and complicated skin and skin-structure infection (7.8%). Moreover, 17.6% of patients had bacteraemia and 47.1% were in intensive care. Ceftolozane/tazobactam was primarily used as directed therapy for Pseudomonas aeruginosa infections (92.2% of patients). Ceftolozane/tazobactam was used because of resistance to (86.3%), failure of (11.8%) or adverse effects from (2.0%) previously prescribed antimicrobials. Ceftolozane/tazobactam susceptibility testing was performed on isolates from 88.2% of patients. Ceftolozane/tazobactam was used in combination with another antimicrobial active against Gram-negative bacilli in 39.2% of patients [aminoglycosides (15.7%), fluoroquinolones (9.8%) and colistin/polymyxin B (7.8%)]. The dosage regimen was customised in all patients based on creatinine clearance. The treatment duration was primarily >10 days (60.8% of patients), with microbiological success in 60.5% and clinical success in 64.4% of patients. Moreover, 7.8% of patients had adverse effects not requiring drug discontinuation. Conclusion: In Canada, ceftolozane/tazobactam is used as directed therapy to treat a variety of severe infections caused by multidrug-resistant P. aeruginosa . It is commonly used in combination with other antimicrobials with relatively high microbiological/clinical cure rates and an excellent safety profile.